Coronary stent deployment to the iliac artery – a complication with a successful treatment - Dziuba, Michał; Lenczewski, Piotr; Chiżyński, Krzysztof; Zielińska, Marzenna; Religa, Wojciech; Kaszyński, Marek; Stefańczyk, Ludomir; Kidawa, Michał (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
We report a description of angioplasty (PCI) of the right coronary artery in a 68-year-old man with stable coronary artery disease and peripheral vascular atherosclerosis. The treatment was complicated by stent dislocation into the substantially narrowed iliac artery without accompanying signs of acute limb ischaemia. Vascular stent implantation was performed in the place of the stenosis of the left external iliac artery with simultaneous crushing of the non-expanded coronary stent into the vessel wall.